THE PROBLEM OF THE NATIONAL CONSCIOUSNESS IN THE NOVEL “DYVYMOSYA V OCHI SMERTI” (“WE ARE LOOKING IN THE EYES OF DEATH”) BY YURII KOSACH - Yurchak, H. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article is devoted to the examination of the existential image of the world created by the writer in the novel, highlighting the peculiarities of the national consciousness. It has been proven that the writer managed to find a balance between the dynamic and intriguing plot regarding the awakening of the national consciousness, and the establishment of the nationhood- thus creating a distinctive type of the adventure novel- a spy novel.